English Teaching Learning by Leveling System Model on Class XI of Vocational High School 3 Samarinda Students - Silaban, Harjon (Educationist: Journal of Educational and Cultural Studies, 2022)
This research implemented Classroom Action Research by three cycles in 2022/2023-year plan. The subject is Dress Making Department of third class XII at Vocational High School 3 Samarinda followed by 21 students, and the object lesson is about Reading Section. Teaching Learning by Levelling System require the similarity of English Skills ability on the certain level of special class by concerning the placement test score divided into 3 kinds of abilities level based on the score achieved by the students. Next step is to choose the suitable Teaching-Learning Method based on students’ English ability level and be concluded by evaluation. Shorts of evaluation be held, one of them is daily performance test that be held at the last of lesson explanation, periodical test that be held at the last of some topic’s explanation, promotion test that be held at the last of semester to follow up and to determine the suitable new student’s ability’s level, and prediction and international TOEIC test to measure the international standard of students’ English ability. The implementation of this teaching- learning model can increase the learning outcomes significantly. It is proved by the increasing of teaching-learning quality more than 75%, start from second cycle (84,5%) and (98,8%) on the third cycle.